Subacute Sclerosing Panencephalitis with Subclinical Infection - V. A. Kotrashetti; Vijay Baburao Sonawane; Kapil Bainade; Nair, Shweta; Amit Vatkar; Kumar, Santosh (Academia Anatomica International, 2020)
Subacute Sclerosing Panencephalitis (SSPE) is a chronic complication of measles. It is a neurodegenerative disorder characterized by cognitive and memory deterioration, behaviour abnormalities, involuntary movements and repetitive myoclonic jerks and a steady motor decline. We report a case of a 7-year-old girl with subacute sclerosing panencephalitis presenting with myoclonic jerks, regression of motor milestones and speech. The child was not immunised for measles. Magnetic resonance imaging revealed multiple variable-sized ill-defined T2W and FLAIR hyperintense areas are seen involving the white matter of the bilateral fronto-parietal lobes. Electroencephalograph findings and CSF analysis confirmed the diagnosis of subacute sclerosing panencephalitis.